Effects of Handshake Duration on Other Nonverbal Behavior. Issue 1 (February 2020) - Nagy, Emese; Farkas, Tibor; Guy, Frances; Stafylarakis, Anna
Although detailed descriptions of proper handshakes partly comprise many etiquette books, how a normal handshake can be described, its proper duration, and the consequences of violating handshake expectations remain empirically unexplored. This study measured the effect of temporal violations of the expected length of a handshake (less than three seconds according to previous studies) administered unobtrusively in a naturalistic experiment. We compared volunteer participants' ( N = 34; 25 females; 9 males; M age = 23.76 years, SD = 6.85) nonverbal behavior before and after (a) a prolonged handshake (>3 seconds), (b) a normal length handshake (average length <3 seconds), and (c) a control encounter with no handshake. Frame-by-frame behavioral analyses revealed that, following a prolonged handshake (vs. a normal length or no handshake), participants showed less interactional enjoyment, as indicated by less laughing. They also showed evidence of anxiety and behavioral freezing, indicated by increased hands-on-hands movements, and they showed fewer hands-on-body movements. Normal length handshakes resulted in less subsequent smiling than did prolonged handshakes, but normal length handshakes were also followed by fewer hands-on-face movements than prolonged handshakes. No behavior changes were associated with the no-handshake control condition. We found no differences in participants' level of empathy or state/trait anxiety related to these conditions. In summary, participants reacted behaviorally to temporal manipulations of handshakes, with relevant implications for interactions in interviews, business, educational, and social settings and for assisting patients with social skills difficulties.